2018
DOI: 10.1021/acssynbio.8b00342
|View full text |Cite
|
Sign up to set email alerts
|

Less Is More: Toward a Genome-Reduced Bacillus Cell Factory for “Difficult Proteins”

Abstract: The availability of complete genome sequences and the definition of essential gene sets were fundamental in the start of the genome engineering era. In a recent study, redundant and unnecessary genes were systematically deleted from the Gram-positive bacterium Bacillus subtilis, an industrial production host of high-value secreted proteins. This culminated in strain PG10, which lacks about 36% of the genome, thus representing the most minimal Bacillus chassis currently available. Here, we show that this “miniB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 31 publications
3
51
0
2
Order By: Relevance
“…This strategy enabled the removal of unnecessary proportions of genome at large scale without causing palpable defects in the target organisms (except in a few instances [135,144]) and sometimes yielded improved cellular performances in terms of growth rates, cell density, transformation efficiency, and protein productivity compared with their wild-type counterparts. With an unintended discovery of the desirable properties that synthetic minimal genomes may convey in microbial production, several studies have explored their potential for industrial applications for recombinant protein production [145][146][147][148]. The following sections have been outlined to elaborate in detail on cellular mechanisms underlying improved performance in genome-reduced strains and some of the practical examples of the minimal genome expression system, and also to discuss potential applications of genome-reduced strains in heterologous protein expressions.…”
Section: Concept and Overview Of Synthetic Minimal Genomementioning
confidence: 99%
See 2 more Smart Citations
“…This strategy enabled the removal of unnecessary proportions of genome at large scale without causing palpable defects in the target organisms (except in a few instances [135,144]) and sometimes yielded improved cellular performances in terms of growth rates, cell density, transformation efficiency, and protein productivity compared with their wild-type counterparts. With an unintended discovery of the desirable properties that synthetic minimal genomes may convey in microbial production, several studies have explored their potential for industrial applications for recombinant protein production [145][146][147][148]. The following sections have been outlined to elaborate in detail on cellular mechanisms underlying improved performance in genome-reduced strains and some of the practical examples of the minimal genome expression system, and also to discuss potential applications of genome-reduced strains in heterologous protein expressions.…”
Section: Concept and Overview Of Synthetic Minimal Genomementioning
confidence: 99%
“…The metabolic burden imposed by expressing heterologous genes arises from competition for shared but limited cellular resources between exogenous genes and host metabolism. Thus, removal of host genes that are nonessential translates to an overall decrease in the resource cost spent on now-absent host metabolism, which then reduces the net metabolic load [159] and allows for efficient resource utilization and protein translation ( Figure 2) [24,137,145]. In addition, reduced genomic complexity in the minimal cells may help to curtail regulatory interference with the targeted or exogenous metabolic pathways [114], reducing the number of compounding variables that pose unknown effects on heterologous expression.…”
Section: Increased Availability Of Cellular Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…This bacterium is also an attractive host for heterologous protein production due to its excellent fermentation and high product yield capacities (van Dijl and Hecker, 2013). Hence, a minimal strain of B. subtilis was engineered (Reuß et al, 2017) for heterologous production of "difficult proteins" natively secreted by Staphylococcus aureus, Aguilar and colleagues demonstrated that these proteins were successfully produced in the genome-reduced, but not in the wild-type strain (Suárez et al, 2019). Nonetheless, information on how the membrane proteome abundances was altered upon the production of this heterologous protein remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have published a study describing a method which simultaneously combines the comprehensiveness of shotgun-MS and the accuracy of targeted-MS, allowing the calculation of absolute membrane protein abundances in a living organism (Antelo-Varela et al, 2019). In the study presented here, we provide absolute membrane protein concentrations of the genome-reduced B. subtilis strain (midiBacillus) IIG-Bs27-47-24 expressing IsaA (Suárez et al, 2019). To engineer this strain, 1401 genes were systematically deleted from the parental strain B. subtilis 168, which represents a genome reduction of 30.95% (Reuß et al, 2017).…”
Section: Introductionmentioning
confidence: 99%